Implications of Pasuruan Regency Regional Regulation Number 1/2021 on Regional Innovation in Improving Local Government Performance - Tri Wicaksono, Agung; Arbi Nur B.J, Achmad; Mar’ah, Sayyidatul; Zami Kautsarani, Rizqina; Safiudin R., Achmad (Department of Constitutional Law, Faculty Sharia and Law, UIN Sunan Ampel Surabaya, 2025)
This study aims to evaluate the effectiveness of Pasuruan Regency Regional Regulation Number 1 of 2021 concerning Regional Innovation in encouraging the birth of new innovations in Pasuruan Regency. The research method employed is a normative legal research approach, supported by primary legal materials in the form of regional regulations and derivative policies, as well as secondary legal materials including interviews with relevant government officials and official government documents. The results of the study revealed that after the implementation of the regulation, several significant innovations emerged and received national recognition, such as KIOS e-PAK LADI which won the Top 30 Public Service Innovation Competition of East Java Province 2021, and KAPITEN Pasuruan Getas Juara which was included in the Top 45 National Public Service Innovations 2022. Other innovations, such as SIAP MASLAHAT and SISTER PERI, also show an improvement in the quality of public services which is reflected in the national awards received. In addition, these innovations make a positive contribution to several key performance indicators, such as the Human Development Index, the Bureaucratic Reform Index, the Regional Governance Index, and the Community Satisfaction Index. These findings show that regional innovation policies have played a significant role in improving the quality of governance and public services in Pasuruan Regency, as well as increasing regional competitiveness.